The effectiveness of the integrated sound-word method to improve the skills in reading, writing and the reading interest of Bahasa Melayu among the pupils with dyslexia - Muhammad Razif, A.A; lsahak, H. (2016)

(untitled)
This study was conducted to examine the effectiveness of Kaedah Gabungan Bunyi Kata (KGBK) - (the integrated sound-word method), to improve the skills in reading, writing of Bahasa Melayu and the reading interest of pupils with dyslexia. The samples of this study consisted of five pupils in a primary school with different levels of dyslexic problem. Two were classified as 'mild', two 'moderate' and one quite 'serious'. The KGBK teaching-and-learning intervention process was conducted for 16 weeks in a school classroom by a teacher trained in KGBK for this purpose. Six data collection methods were used: observation and recording, interviews with the teacher and students, student's works, teacher reflection notes, video recordings and four periodic KGBK tests. The data were analysed to answer the research questions stated earlier. The findings show that the KGBK approach used to teach these five dyslexic pupils was effective in increasing their proficiency in reading and writing of Bahasa MeIIlYU.Their interest in 2R also increased: they were motivated to learn to read and write. However, the increase varies according to the level of the dyslexic problems experienced by these pupils. Subject B (mild dyslexia) was able to read and write up to Level 8 in the KGBK tests, involving the use of diphthong words. Another 'mild dyslexia' subject C was able to read and write up to level 7, which involved closed syllable words 'ng'. Subjects A and D (moderate dyslexia) was able to read and write up to level 6, which involved words with two different 'e' sounds and '0'. Even subject E (serious dyslexia) was able to read and write up to level 6, The results also show that all five. subjects enjoyed learning the 2R. They feel motivated